Thermal behaviour of ski-boot liners: Effect of materials on thermal comfort in real and simulated skiing conditions. - Colonna, M.; Moncalero, M.; Nicotra, M.; Pezzoli, A.; Fabbri, E.; Bortolan, L.; Pellegrini, B.; Schena, F. (Procedia Engineering, 2014)
The choice of the appropriate material for the construction of ski-boot liners is of fundamental importance in order to achieve ergonomic comfort and high thermal insulation. In this work the effect on thermal comfort of different materials used for commercial ski-boot liners has been analysed. The thermal insulation and the moisture management of liners made of different materials have been tested both in a climatic chamber and in outdoor conditions using wireless sensors combined with infrared thermography. The results obtained show substantial differences in terms of thermal comfort between the liners in the same environmental conditions, showing that closed cell ethylene vinyl acetate foams provide the best thermal comfort.